Pembelajaran Materi Pendidikan Agama Islam (PAI) Berwawasan Multikultural - Ellyana Ellyana (At-Ta'lim : Media Informasi Pendidikan Islam, 2019)
Abstract: Learning Islamic Religious Education Material with Multicultural Insights In some educational institutions it is often not realized that they have implemented policies that are not evenly distributed towards all groups, or are a bit discriminatory. The concept of Multicultural Islamic Religious Education exists to overcome this. So that in understanding the basic values of multiculturalism starting from an inclusive attitude towards differences, respecting, democracy, tolerance, respecting the work of others, attitudes prioritize unity and unity in a community or community that has different ethnic, religious, cultural backgrounds, status economics and others, so that ultimately students are expected to be able to practice these attitudes in daily life. Learning methods of Islamic Religious Education with Multicultural Insights in question consists of three things, namely the strategy of organizing learning, learning delivery strategies, and learning management strategies.Abstrak: Pembelajaran Materi Pendidikan Agama Islam (PAI) Berwawasan Multikultural  Pada beberapa institusi pendidikan sering tidak disadari telah menerapkan kebijakan yang tidak sama rata terhadap semua kalangan, atau sedikit diskriminatif. Konsep Pendidikan Agama Islam Multikultural hadir untuk mengatasi hal tersebut. Sehingga dalam memahami nilai-nilai pokok multikultural mulai dari sikap inklusif terhadap perbedaan-perbedaan, menghormati,  demokrasi, toleransi, menghargai hasil karya orang lain, sikap mengutamakan persatuan dan kesatuan dalam suatu komunitas atau masyarakat yang berbeda latar belakang suku, agama, budaya, status ekonomi dan lain-lain, sehingga pada akhirnya siswa diharapkan mampu mempraktekkan sikap-sikap tersebut dalam kehidupan sehari-hari. Metode pembelajaran Pendidikan Agama Islam (PAI) Berwawasan Multikultural yang dimaksud terdiri dari tiga hal, yaitu strategi pengorganisasian pembelajaran, strategi penyampaian pembelajaran, dan strategi pengelolaan pembelajaran.